Quantification of lateral heterogeneity in carbohydrate permeability of isolated plant leaf cuticles - Remus-Emsermann, Mitja N.; de Oliveira, Sheron; Schreiber, Lukas; Leveau, Johan H. (Frontiers in Microbiology, 2011)
In phyllosphere microbiology, the distribution of resources available to bacterial colonizers of leaf surfaces is generally understood to be very heterogeneous. However, there is little quantitative understanding of the mechanisms that underlie this heterogeneity. Here, we tested the hypothesis that different parts of the cuticle vary in the degree to which they allow diffusion of the leaf sugar fructose to the surface. To this end, individual, isolated cuticles of poplar leaves were each analyzed for two properties: 1) the permeability for fructose, which involved measurement of diffused fructose by gas chromatography and flame ionization detection (GC-FID), and 2) the number and size of fructose-permeable sites on the cuticle, which was achieved using a green fluorescent protein (GFP)-based bacterial bioreporter for fructose. Bulk flux measurements revealed an average permeance P of 3.39x10-9 m s-1, while the bioreporter showed that most of the leaching fructose was clustered to sites around the base of shed trichomes, which accounted for only 0.37 % of the surface of the cuticles under study. Combined, the GC-FID and GFP measurements allowed us to calculate an apparent rate of fructose diffusion at these preferential leaching sites of 9.2x10-7 m s-1. To the best of our knowledge, this study represents the first successful attempt to quantify cuticle permeability at a resolution that is most relevant to bacterial colonizers of plant leaves. The estimates for P at different spatial scales will be useful for future models that aim to explain and predict temporal and spatial patterns of bacterial colonization of plant foliage based on lateral heterogeneity in sugar permeability of the leaf cuticle.